2023
DOI: 10.3389/fenrg.2023.1177437
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-flow pump performance improvement based on circulation method

Abstract: Mixed-flow pumps have been extensively employed in daily life, improving their energy characteristics contribute to the reduction of energy consumption worldwide. In this study, to overcome the decrease of optimization upper limit caused by using a single type of parameter as the design parameter, a typical mixed-flow pump was chosen for study, and its impeller was parameterized by five geometric and eight hydrodynamic parameters. With head and efficiency as the constraint and optimization objective respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Ling Bai et al [22] highlighted the performance improvement of an EPS impeller based on the Taguchi approach and found that the front and rear shrouds of the impeller meridian significantly affect the ESP performance. Chen et al [23] studied performance improvement of a mixed-flow pump based on the entropy production method. They found that the geometric and hydrodynamic parameters greatly influenced the pump's energy characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Ling Bai et al [22] highlighted the performance improvement of an EPS impeller based on the Taguchi approach and found that the front and rear shrouds of the impeller meridian significantly affect the ESP performance. Chen et al [23] studied performance improvement of a mixed-flow pump based on the entropy production method. They found that the geometric and hydrodynamic parameters greatly influenced the pump's energy characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Ling Bai et al [22] highlighted the performance improvement of the EPS impeller based on the Taguchi approach, and the result found that the front and rear shroud of the impeller meridian significantly affects the ESP performance. Chen et al [23] studied performance improvement based on the entropy production method of a mixed-flow pump. Results found that the geometric and hydrodynamic parameters greatly influenced the pump's energy characteristics.…”
Section: Introductionmentioning
confidence: 99%